2010
DOI: 10.4049/jimmunol.1002204
|View full text |Cite
|
Sign up to set email alerts
|

Does Cytolysis by CD8+ T Cells Drive Immune Escape in HIV Infection?

Abstract: CD8+ “cytotoxic” T cells are important for the immune control of HIV and the closely related simian models SIV and chimeric simian–human immunodeficiency virus (SHIV), although the mechanisms of this control are unclear. One effect of CD8+ T cell-mediated recognition of virus-infected cells is the rapid selection of escape mutant (EM) virus that is not recognized. To investigate the mechanisms of virus-specific CD8+ T cell control during immune escape in vivo, we used a real-time PCR assay to study the dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
(68 reference statements)
4
26
0
1
Order By: Relevance
“…In addition, the in vivo dynamics may be different following infection of other cell types, including CD4 cells that are not recently activated. However, the similarity between the death rate of infected cells we observe in vitro and that estimated in vivo is consistent with arguments that CD8 ϩ T cells may not affect the death rate of productively infected cells (29)(30)(31).…”
Section: Discussionsupporting
confidence: 71%
“…In addition, the in vivo dynamics may be different following infection of other cell types, including CD4 cells that are not recently activated. However, the similarity between the death rate of infected cells we observe in vitro and that estimated in vivo is consistent with arguments that CD8 ϩ T cells may not affect the death rate of productively infected cells (29)(30)(31).…”
Section: Discussionsupporting
confidence: 71%
“…Such a nonlytic T cell response should be able to select for viral escape. Recent studies suggest that nonlytic control of virus replication may be the major mechanism of suppression of SIV replication in monkeys (13,53,98). Importantly, this model predicts a slower accumulation of the escape variant if the total magnitude of the CD8 ϩ response is high (Fig.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Studies conducted by us and others have shown that depletion of CD8 ϩ lymphocytes in SIV-infected RMs followed by ART treatment did not alter the life span of productively SIV-infected cells or impact viral decay kinetics compared to undepleted animals (26,27). In addition, decay rates of wild-type and escape mutant virus were found to be similar during the acute phase of simian-human immunodeficiency virus (SHIV) infection of macaques (28). Suppression of HIV replication by CD8 ϩ T cells via noncytolytic mechanisms that inhibit virus transcription was first observed by Levy and colleagues in 1986 (29,30), although the molecular mechanisms underlying this antiviral activity have remained elusive (31)(32)(33).…”
mentioning
confidence: 75%